Influence of impurity defects on vibrational and electronic structure of graphene. Issue 2 (13th March 2013) - Sagalianov, I.Y.; Prylutskyy, Y.I.; Tatarenko, V.A.; Radchenko, T.M.; Sudakov, O.O.; Ritter, U.; Scharff, P.; Le Normand, F.
Abstract Using the ab initio methods, boron or nitrogen doping effects on the characteristics of electron and vibrational spectrums of graphene are studied. We revealed that a mutual arrangement at the largest distance from each other is energy‐preferred for these dopant atoms. Depending on their kind, one can regulate conductance and raise values of fundamental frequencies of the Raman scattering in graphene.